Using critical care physicians to deliver anesthesia and boost surgical caseload in austere environments: the Critical Care General Anesthesia Syllabus (CC GAS). Issue 6 (June 2020) - Tran, Quincy K.; Mark, Natalie M.; Losonczy, Lia I.; McCurdy, Michael T.; Lantry, James H.; Augustin, Marc E.; Colas, Lovely N.; Skupski, Richard; Toth, Arthur S.; Patel, Bhavesh M.; Zimmer, Donald F.; Tracy, Rebecca; et al.
Abstract: Background: Despite an often severe lack of surgeons and surgical equipment, the rate-limiting step in surgical care for the nearly five billion people living in resource-limited areas is frequently the absence of safe anesthesia. During disaster relief and surgical missions, critical care physicians (CCPs), who are already competent in complex airway and ventilator management, can help address the need for skilled anesthetists in these settings. Methods: We provided a descriptive analysis that CCPs were trained to provide safe general anesthesia, monitored anesthesia care (MAC), and spinal anesthesia using a specifically designed and simple syllabus. Results: Six CCPs provided anesthesia under the supervision of a board-certified anesthesiologist for 58 (32%) cases of a total of 183 surgical cases performed by a surgical mission team at St. Luc Hospital in Port-au-Prince, Haiti in 2013, 2017, and 2018. There were no reported complications. Conclusions: Given CCPs' competencies in complex airway and ventilator management, a CCP, with minimal training from a simple syllabus, may be able to act as an anesthesiologist-extender and safely administer anesthesia in the austere environment, increasing the number of surgical cases that can be performed. Further studies are necessary to confirm our observation. Abstract : Public Health; Surgery; Critical Care; Intensive Care Medicine; Clinical Research; austere environment; anesthesiologist extender; anesthesia